Let u be 4 + 2 + -1 + 0. Suppose -u*m + 15 = -5. Solve x = -0*x + m for x.
4
Let q = 9 - 7. Let n(f) = -f + 0*f3 - 2*f2 + f3 - 4*f2 - q*f**3. Let g be n(-6). Solve -5*s - 4 - g = 0 for s.
-2
Let s(u) = -u**2 - 4*u + 2. Let d be s(-4). Solve d*x = 14 - 8 for x.
3
Suppose 0 = -x - 1. Let i be x + 0 + 6 + 0. Solve -18 = -i*a + 2 for a.
4
Let x = 12 + 6. Suppose -x = -3*k + 2*k. Suppose -s + 6 = v + 4*v, -2*s - k = -5*v. Solve 0 = 3*p + v - 17 for p.
5
Let u = -105 - -48. Let b = u - -41. Let d = -8 - b. Solve 3*i - d = -i for i.
2
Suppose 4*o + 1 = 4*h + 5, 0 = 4h + o - 6. Let t be h((0 - 2) + -1). Let a be (t/9)/(3/(-117)). Solve -4*z = -a - 7 for z.
5
Let w be 8/(-12)*-1*21. Solve 5*s = -4 + w for s.
2
Suppose -2*s - 3*c = 3*s + 41, 5*s + 27 = 4*c. Let b = 10 + s. Solve b + 1 = -4*r for r.
-1
Let d be 5/(2*(-5)/(-10)). Solve 4*q - 3*q = d for q.
5